THE IMPLEMENTATION OF PRINCIPLES IN MAKING DIVORCE DIFFICULT AS THE GENERAL EXPLANATION OF LAW NUMBER 1 0F 1974 CONCERNING MARRIAGE IN SERUI RELIGIOUS COURT - Muhammad Ilham (JICSA : Journal of Islamic Civilization in Southeast Asian, 2020)
The purpose of this study was to determine and find out how the application and form of implementation of the principle of complicating divorce cases in the Class II Serui Religious Court. The data sources of this research are divorce case documents ranging from lawsuit/divorce applications, BAS (Session Minutes), and decisions or decisions issued by the panel of judges. This research is qualitative descriptive field research that takes place in Class II Serui Religious Court. The approach used is the juridical, syar'i, anthropological, and sociological approaches. The data collection obtained in the field is by analyzing observation techniques, interviews, and documentation. The results of this study indicate that in general the principle of complicating divorce in the Serui Religious Court is quite good, this is inseparable from the free time available for the assembly and mediator to reconcile husband and wife in divorce proceedings.